2000
DOI: 10.1034/j.1600-0765.2000.035001042.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage conditions of avulsed teeth affect the phenotype of cultured human periodontal ligament cells

Abstract: After severe injury to the periodontal ligament (PL), the phenotypes of cells recolonizing root surfaces influence the extent and type of repair processes. In teeth that are replanted following avulsion injury, recolonization of the PL space by osteogenic cells instead of by PL fibroblasts may favor bone formation (i.e. ankylosis) instead of PL regeneration. We consider here that recolonization processes depend in part on the storage conditions of the teeth following avulsion. We used an in vitro cell culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…In contrast, only a few investigations on the precise mechanisms have been reported with regard to the relationship between tooth implantation or replantation and regeneration of the periodontal ligament (Iqbal and Bamaas, 2001;Kawanami, et al, 2001;Lekic et al, 2001;Lin et al, 2000).…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, only a few investigations on the precise mechanisms have been reported with regard to the relationship between tooth implantation or replantation and regeneration of the periodontal ligament (Iqbal and Bamaas, 2001;Kawanami, et al, 2001;Lekic et al, 2001;Lin et al, 2000).…”
Section: Introductionmentioning
confidence: 81%
“…To date, most replantation studies have focused on factors such as extraoral period, storage media for tooth, timing of endodontic treatment, duration of root canal medication and development of healing complications (Hiremath and Kidiyoor 2011; Lekic et al 1998; Lin et al 2000). Andreasen reported that the decisive factor for PDL healing was immediate replantation (Andreasen et al 1995) indicating that if the teeth are not replanted immediately, they will most probably be lost due to root resorption or infraocclusion (Andreasen et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, we now know these cells to be hematopoietic stem cells (HSCs), the first described adult stem cell, although one could argue for the muscle-derived satellite cell described in 1961 to take this title (Mauro, 1961; Moss and Leblond, 1971). From the work of McCulloch and Till, the adult stem cell field gathered momentum in the late sixties and early seventies as patients suffering from SCID (severe combined immunodeficiency) were treated using bone marrow transplants or HSC concentrates (Dicke and van Bekkum, 1973; Lin et al , 2000). In 1978, HSCs were identified in umbilical cord blood and a new population of adult stem cells was born: the umbilical cord blood stem cell (Emerson et al , 1985; Broxmeyer et al , 1990).…”
Section: Adult Stem Cells and The Asc: A Brief Historymentioning
confidence: 99%